Herhistorisering en herposisionering: perspektiewe op aspekte van geskiedsbeoefening in hedendaagse Suid-Afrika (Historia, 2021)
Rehistoricising and repositioning: perspectives on aspects of historical practice in contemporary South Africa This article comments critically on certain aspects of the involvement of the African National Congress government with historical practice in South Africa. It highlights the weaknesses of nationalistic inspired political histories and the shortcomings of the history report authored by the Truth and Reconciliation Committee. In a concluding section it seeks to reposition the discipline as practised at predominantly Afrikaans universities.